(untitled) (Journal of history, 2020)
In this article, the author tried to give a detailed description and semantic meaning of the image of lion’s faces, depicted on bracelets of the Golden Horde era of Northern Kazakhstan. The main purpose of the article is to define the image of a lion, and his appearance in the decorative arts of medieval Kazakhstan. In the quality of the jewelry, bracelets with the image of lion’s faces found during excavations of the necropolis of Bozok in Central Kazakhstan were chosen. A pair of silver bracelets depicting lion masks found on the wrists of a woman’s hands; the burial dates from the XIII – early XIV centuries. Bracelets clearly demonstrate the level of trade relations of the time. Of great interest to silver bracelets with the image of lion’s faces is the problem of early dating, genesis and fine styling, which allows to identify the continuity of traditions, the processes of formation of the Golden Horde «imperial» style and the role of local and regional art centers in it. Not excluded the possibility that the motive of the lion’s faces is an echo of the once famous «animal style», however, continues to be popular in the art of medieval Islam. Silver bracelets with lion’s faces are an important decoration of the women’s costume of nomads Ulus Juchi and were widely used by representatives of high social status in society